Characterisation of vitellogenin and vitellin of Fenneropenaeus merguiensis (De Man) - Zacharia, Sherly; Kakati, V S (Indian Journal of Fisheries, 2011)
Purification and characterisation of vitellogenin and vitellin from haemolymph and mature ovaries respectively of Fenneropenaeus merguiensis were conducted using ammonium sulphate precipitation technique. The vitellogenin level inthe haemolymph was low in the early stages of development, but increased significantly in the late maturing stages (Stage III) and fell abruptly in spent females. Purified vitellogenin had an approximate molecular weight of 350kDa as determined by PAGE and was characterised as lipoglycoprotein with calciumaffinity on the basis of staining data. Two forms of purified vitellin (Vn1 and Vn2) of molecular weights 550 and 300kDa were also isolated. Vn1 was characterised as a lipo-glyco-calcium complex while Vn2 was glycoprotein in nature based on staining data. SDS PAGE analysis revealed 6 subunits inpurified vitellogenin and 5 subunits in vitellin.